Oxidative stress is involved in the activation of NF-κB signal pathway and immune inflammatory response in grass carp gill induced by cypermethrin and/or sulfamethoxazole - Li, Baoying; Wang, Yu; Zhao, Hongjing; Yin, Kai; Liu, Yachen; Wang, Dongxu; Zong, Hui; Xing, Mingwei (Environmental science and pollution research international, 2022)
At present, the concentration of environmental pollutants, such as pesticides and antibiotics exposed in environment, especially in aquatic environment is increasing. Research on environmental pollutants has exploded in the last few years. However, studies on the combined effects of pesticides and antibiotics on fish are rare, especially the toxic damage to gill tissue is vague. In this paper, cypermethrin (CMN) and sulfamethoxazole (SMZ) were analyzed and found that there was a strong correlation between the pathways affected by the first 30 genes regulated by CMN and SMZ, respectively. Therefore, the toxic effects of CMN (0.651 μg L −1 ) and/or SMZ (0.3 μg L −1 ) on grass carp gill were studied in this paper. Histopathology, quantitative real-time PCR, and other methods were used to detect the tissue morphology, oxidative stress level, inflammation, and apoptosis-related indicators of the fish gills after exposure of 42 days. It was found that compared with the single exposure (CMN/SMZ) group, the combined exposure (MIX) group had a more pronounced oxidative stress index imbalance. At the same time, nuclear factor-κB (NF-κB) signal pathway was activated and immuno-inflammatory reaction appeared in MIX group. The expression of tumor necrosis factor (TNF-α) in the rising range is 2.94 times that of the C group, while the expression of interleukin 8 (IL-8) is as high as 32.67 times. This study reveals the harm of CMN and SMZ to fish, and provides a reference and basis for the rational use of pesticides and antibiotics.